Artificial intelligence in shipping : the state of digital innovation - Lambrou, Maria (Routledge, Taylor & Francis Group, 2025)
The book addresses strategic and innovation management matters that emerge with AI technology deployment in shipping. It illustrates the making of an AI-powered shipping operation as a process; advances in AI technology as well as trustworthy design and development principles and practices can frame, inspire, and guide the contextualized AI-instigated shipping digitalization.The volume elaborates on foreseen value aggregation models stemming from the AI and human symbiosis possibilities, and the consequences these developments imply for shipping business organizations and markets. Preemptive value creation models are exemplified, including endeavours for deep shipping knowledge creation, shipping business process augmentation for both low-discretion and high-criticality tasks, and autonomous vessel and maritime infrastructures establishment, as well as new AI-supply side oriented business models. The author posits that AI-driven renewal strategies do not imply a disinvestment in 'legacy' functions (aka ship ownership and management) paired with aggressive investment in AI development and platformization; AI management directs a new mix of conceivable physical and digital assets, resources, and capabilities for the chosen nuance of a firm's business model innovation. The central argument of the book elaborates how shipping companies in the loop can be nothing but the negotiated outcome of a new AI-powered institutional entrepreneurial regime; embedded, distributed agency mechanisms enact the wealth-creating, progressive, and responsible digitalization of shipping.This volume will be of value to students and researchers interested in shipping markets, digital technology, and innovation management.
Keywords: Shipping -- Technological innovations.; Transportation -- Technological innovations.; Artificial intelligence.; elektronické knihy; electronic books